Strategi Keberlanjutan Baitul Maal Wat Tamwil di Kota Yogyakarta Dengan Metode Analytical Network Process - Khairunnisa, Inas; Mukhsin, Muhamad; Roni, Abdul (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
The purpose of this research is to find out the problems to the sustainability strategy of BMT in the city of Yogyakarta so that it can operate in the long term. This study uses the Analytical Network Process (ANP) method with a sample of 9 people consisting of BMT practitioners, academics, and regulators. This research is a descriptive qualitative research. This research shows that priority issues that need to be addressed are: 1) Regulation and supervision, 2) Market/communal, 3) Management, 4) Human Resources (HR), 5) Infrastructure. Experts agree that the priority solution is the regulatory and supervisory aspect with a rater agreement value of W = 0.4907. While there are five strategies, namely 1) Optimizing the role of the government, especially to support the sustainability of BMT, 2) Improving the HR education system that is integrated into Islamic economics in theory and practice, 3) Development of institutional and operational infrastructure, 4) Outreach to the community in collaboration with relevant stakeholders, 5) Development of monitoring system and reporting system. The respondents have varied opinions with a value of W = 0.2145. This research has implications for the theory of BMT and BMT sustainability problems in the city of Yogyakarta, the policies taken to support the existence of BMT.